2016
DOI: 10.1101/052803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel independence test for somatic alterations in cancer shows that biology drives mutual exclusivity but chance explains co-occurrence

Abstract: Just like recurrent somatic alterations characterize cancer genes, mutually exclusive or co-occurring alterations across genes suggest functional interactions. Identifying such patterns in large cancer studies thus helps the discovery of unknown interactions. Many studies use Fisher's exact test or simple permutation procedures for this purpose. These tests assume identical gene alteration probabilities across tumors, which is not true for cancer. We show that violating this assumption yields many spurious co-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Mutual exclusivity of various alterations was statistically assessed using the DISCOVER R package (v0.9.3) 41 . All p-values derived from multiple testing were corrected using built-in false discovery rate (FDR).…”
Section: Mutual Exclusivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Mutual exclusivity of various alterations was statistically assessed using the DISCOVER R package (v0.9.3) 41 . All p-values derived from multiple testing were corrected using built-in false discovery rate (FDR).…”
Section: Mutual Exclusivity Analysismentioning
confidence: 99%
“…c, Mutual exclusivity of copy number losses of chromosome arms 17p, 16q, and 8q. Significance was assessed using the impurity test for mutual exclusivity, implemented in the R package DISCOVER 41 .…”
Section: Code Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the proportion of genes with mutations in different senescence subtypes, and we compared the differences in the top 10 mutated genes in the three senescence subtypes using the chi-square test. Since existing studies have reported that exclusive or co-occurring somatic changes in cancer can indicate functional interactions, 57,58 we also explored the mutual exclusion or coexistence of genes in three senescence subtypes. According to a previous study, 32 10 canonical signaling pathways consisting of 335 genes were evaluated as oncogenic pathways (Table S4).…”
Section: Mutation Landscape Of Crc Senescence Subtypesmentioning
confidence: 99%
“…31 Genetic lesion co-occurrences and mutual exclusions were computed using the R package DISCOVER available on Bioconductor with the default parameters. 32…”
Section: Next-generation Sequencing Copy Number and Molecular Analysesmentioning
confidence: 99%